La problématique éthique du développement de l’aquaculture industrielle au Canada : analyse mésologique d’un nouveau rapport possible à l’océan - Louis-Etienne Pigeon; Lyne Létourneau (VertigO)
Aquaculture development in Canada is a recent and important phenomenon. As an economic activity, aquaculture has the potential to compensate for the rapid loss of marine resources that have made the country’s reputation for centuries. But the development of aquaculture farms and the possibility to introduce new biotechnological techniques and products – such as the transgenic salmon – has provoked social opposition from various organizations and interest groups directed towards the investors and promoters of this new industry. This article aims at analyzing, from an ethical perspective, the possibilities of aquaculture in this context. The method involved is inspired from a « mesology », meaning that it focuses primarily on the human beings’ relation to nature. We argue that the development of aquaculture in Canada could be a beneficial strategy because it creates new places of contact between men and nature through a relation of domestication. Nevertheless, the introduction of high-tech methods such as transgenic manipulations can reduce the quality and the diversity of these relations because they are essentially modern techniques.